Digital Transformation through Mobile Applications: Innovative Strategies to Enhance MSME Management and Growth in Indonesia - Manap, Abdul; Yusnindar; Rijal, Syamsu (Technology and Society Perspectives (TACIT), 2024)
Digital transformation through mobile applications has become a strategic necessity to improve the management and growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to analyze the role of mobile applications in facilitating operational efficiency, business model innovation, and market expansion for MSMEs. Using a qualitative literature review approach, data were sourced from 22 selected articles published between 2015-2024 on Google Scholar. Descriptive analysis reveals that applications like GoBiz, TaniHub, and Qasir help MSMEs enhance management efficiency and market access. However, challenges such as low digital literacy and limited infrastructure remain significant obstacles. This research underscores the importance of synergy between the government, private sector, and MSMEs to optimize the benefits of digital transformation. The findings provide practical implications for government policies, application developers' innovations, and MSMEs' adaptation strategies in the digital era